Direito ao esquecimento e liberdade de expressão: posicionamento do STJ nos casos “Chacina na Candelária” e “Aída Curi”. - Oliveira, Nara Fonseca de Santa Cruz (2017)
With the development of new technologies, we are currently experiencing a revolution in the information society. The Internet has provided greater global integration and has completely altered the recall process, given that the facts posted on the web tend to be timeless and it is not subject to the common biological process of forgetting. In this context, some conflicts were brought to the Judiciary, involving, on the one hand, the supposed "right to forget" (linked to the rights of the personality) and, on the other, the right to freedom of expression and communication. In this work, two cases involving the so-called "right to oblivion" ("Chacina da Candelária" and "Aída Curi") will be studied, both judged on the same day, by STJ, under the report of Minister Luis Felipe Salomão. The factual context of the cases in question was analyzed separately, but the grounds of the decisions were dealt with together, since the High Court used the same arguments to make both decisions, although the solutions pointed out were different: in the case "Chacina da Candelária" (REsp. No. 1,334,097 / RJ), the STJ first applied the right to forgetfulness, since the "Aída Curi" Case (REsp. No. 1,335,153 / RJ) was considered an unforgettable one. In this work, we will analyze the position adopted by the Supreme Court in these cases, discussing whether the way the right to forgetfulness was conceived represents a threat to the right to freedom of expression and communication and the right to collective memory. In order to elucidate the problem, the general aspects involving personality rights, the right to freedom of expression and the collision of fundamental rights will be observed. The institute of collective memory will also be studied.